The Role of Micro-financing in Rural Poverty Reduction in Developing Countries - Momoh Juanah (Hochschule Wismar, Fachbereich Wirtschaft, 2005)
Throughout the developing world, there is a desperate quest for a way out of the financial predicament confronting the rural poor. In most countries of the developing regions, especially South Asia and Sub-Saharan Africa, the rural population forms the larger proportion of the entire population and poverty is prevalent among them. According to the International Fund for Agricultural Development (IFAD 2001), in an assessment of poverty in West and Central Africa, poverty in West and Central Africa is essentially a rural phenomenon with three quarters of the population being located in rural areas. Following the theoretical methodology, this study has examined the role of microfinance in developing countries and has described some measures which can enhance the effectiveness and efficiency of microfinance as an instrument for reducing rural poverty in developing countries. The thesis of this study is that with a well planned and coordinated institutionalized microfinance system operating within the appropriate legal and policy framework, the rural poor may be able to get out of the chronic poverty trap that plagues their lives. By means of a review of relevant literature and a conceptual framework on poverty in general, rural poverty in particular and microfinance services and institutions in the developing countries (using the cases of selected countries), the increase in popularity of microfinance as an instrument for addressing the problem of rural poverty in most developing countries was discovered. Although there is empirical evidence that microfinance can contribute immensely to improving the lives of the rural poor, much evidence points to the fact that the impact of microfinance on the lives of the poorest of the poor is yet to be up to the expectations of developers. Existing evidence also indicate that microfinance services, such as savings, insurance, money transfers, entrepreneurial training and so on, which are more attractive to this class of clients, are yet to be provided. Regulation and supervision is deemed to inhibit the operation of the market but in the case of rural microfinance provision a reasonable amount of regulation and supervision is discovered to be necessary, particularly to protect the mostly illiterate rural poor, from usury interest rates, for example. In all the selected countries and most other developing countries, government regulation and supervision of microfinance operations are present, either directly or indirectly. This paper is sub-divided into five chapters. In Chapter one, the problem, objectives, study area and the research questions of the study are presented. In Chapter two, the research is operationalized through the formulation of a framework of the research methodology. The case study approach which is the major analysis approach for this study is discussed in-depth in this section. Existing literature and studies on rural poverty and microfinance are reviewed in Chapter three. Also in this chapter, microfinance practices in four countries in the developing regions, Bolivia, Ethiopia, Ghana and the Philippines, selected at random are discussed. Chapter Four examines the contribution of microfinance to rural poverty reduction under the various categories of services which include credit, savings, insurance and money transfers. In Chapter five, recommendations are advanced for improving on the provision of microfinance in order for its full impact on rural poverty to be realized.
Keywords: 330; Mikrofinanzierung; Ländlicher Finanzmarkt; Ländliche Armut; Armutspolitik; Entwicklungsländer